Effect of a Semi-Purified Oligosaccharide-Enriched Fraction from Caprine Milk on Barrier Integrity and Mucin Production of Co-Culture Models of the Small and Large Intestinal Epithelium - Alicia M. Barnett (Nutrients, 2016)
Caprine milk contains the highest amount of oligosaccharides among domestic animals, which are structurally similar to human milk oligosaccharides (HMOs). This suggests caprine milk oligosaccharides may offer similar protective and developmental effects to that of HMOs. However, to date, studies using oligosaccharides from caprine milk have been limited. Thus, this study aimed to examine the impact of a caprine milk oligosaccharide-enriched fraction (CMOF) on barrier function of epithelial cell co-cultures of absorptive enterocytes (Caco-2 cells) and mucus-secreting goblet cells (HT29-MTX cells), that more closely simulate the cell proportions found in the small (90:10) and large intestine (75:25). Treatment of epithelial co-cultures with 0.4, 1.0, 2.0 and 4.0 mg/mL of CMOF was shown to have no effect on metabolic activity but did enhance cell epithelial barrier integrity as measured by trans-epithelial electrical resistance (TEER), in a dose-dependent manner. The CMOF at the maximum concentration tested (4.0 mg/mL) enhanced TEER, mucin gene expression and mucin protein abundance of epithelial co-cultures, all of which are essential components of intestinal barrier function.